The higher education project = (The World Bank in Vietnam (WB), 2003)
The Higher Education Project seeks to: a) increase coherence, flexibility, and responsiveness of higher education to the changing demands of society and the market economy; b) improve efficiency and resource utilization in higher education; and c) improve the quality of curriculum, teaching, learning, and research in higher education. The project consists of three components. The first component focuses on capacity building, institutional development, and computerization. In this component, system-level planning and coordination are targeted on the central agencies responsible for higher education. Institutional-level planning improvements are targeted to universities and other higher education institutions. The component will also support development of information technology in participating universities and higher education institutions. The second component will provide grants, on a competitive basis, to support quality improvements in selected qualifying higher education institutions and universities. The selected improvement programs will focus on teaching, learning, research, and institutional administration. The third component provides the essential coordination, implementation, procurement, contract management and accounting functions needed for project implementation